Tema Budaya Kerja dalam Anekdote Zur Senkung Der Arbeitsmoral Karya Heinrich Böll - Khairunnisa Khairunnisa; Syamsu Rijal; Burhanuddin Burhanuddin (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract. Indonesia has just been excluded from the group of developing countries in 2021, while Germany has long been a developed country and continues to develop rapidly so it is hoped that it will serve as an example in terms of its work culture. This research is based on the study and analysis of the text. Heinrich Böll as an influential writer of his time, precisely in 1963, created the Anecdote zur Senkung der Arbeitsmoral which reflected the society of his time. Understand socialism and capitalism-liberalism that reflects the working culture habits of East Germany and West Germany. West German capitalism liberalism is to build relations with foreign companies and mutually beneficial, strategic and disciplined in every work but only concerned with himself. Meanwhile, East German socialism upholds the mercy of others, resulting in a slump in the economy. The social function of this literary work contains entertaining meaning and satire. The anecdote zur Senkung der Arbeitsmoral can be used as a material for discussion on learning German in high school (SMA) and an insight to the reader about German work culture. Keywords: Literary Works, Anecdotal Texts, Work Culture